Praja Mulud in Ramban Biak: Ritual Memory, Cultural Values, and Community-Based Heritage Preservation - Mariyana Asri Dwiyanti; Abdul Hafiz; Suhupawati Suhupawati (Universitas Hamzanwadi, 2024)
This study reconstructs the historical genealogy, ritual sequence, cultural values, and preservation mechanisms of Praja Mulud in Ramban Biak Village, Lenek District, East Lombok. The tradition is an annual community celebration of the Prophet Muhammad’s birth that combines Islamic devotion, Sasak cultural expressions, collective food preparation, the procession of Sabuk Belo, pepaosan, medicinal-oil making, religious instruction, and social care. A qualitative historical method was applied through four stages: heuristics, source criticism, interpretation, and historiography. Data were obtained from observation, documentation, and interviews with customary, religious, community, youth, and village-government figures. The findings show that the exact beginning of Praja Mulud cannot be fixed to a single date because its history survives through plural oral memories. Nevertheless, collective narratives consistently connect its development with the Yayasan Amal Saleh and the leadership legacy of the late Rahil. The tradition endures because it functions simultaneously as religious commemoration, embodied historical memory, social solidarity, intergenerational education, and community identity. Its continuity is supported by voluntary participation and differentiated community roles, but it is challenged by generational distance, inconsistent institutional support, contested religious interpretations, limited documentation, and the risk of reducing living heritage to spectacle. Sustainable safeguarding therefore requires community ownership, youth apprenticeship, systematic oral-history and audiovisual documentation, transparent village collaboration, and cautious cultural promotion that protects ritual authority and local meaning.